2016
DOI: 10.1136/archdischild-2016-310651
|View full text |Cite
|
Sign up to set email alerts
|

Cardiopulmonary exercise testing in children with cystic fibrosis: one centre's experience

Abstract: 1Background 2

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
18
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 34 publications
3
18
0
1
Order By: Relevance
“…Relative and similarly preserved peak _ VO 2 was found in our study groups. While most of the studies reported reduced exercise capacity in CF patients, some found normal values, mainly in pediatric patients with relatively preserved pulmonary function [9,10,28,29]. In our group of mild-moderate CF patients, peak _ VO 2 was preserved potentially due to the relatively young cohort and disease severity.…”
Section: Discussionmentioning
confidence: 49%
“…Relative and similarly preserved peak _ VO 2 was found in our study groups. While most of the studies reported reduced exercise capacity in CF patients, some found normal values, mainly in pediatric patients with relatively preserved pulmonary function [9,10,28,29]. In our group of mild-moderate CF patients, peak _ VO 2 was preserved potentially due to the relatively young cohort and disease severity.…”
Section: Discussionmentioning
confidence: 49%
“…In addition, supramaximal verification, as advocated by Williams et al, seems not to be clinically feasible, at least in our center experience, and a comprehensive response to its use, as well as for the use of secondary criteria to validate a maximal effort, has already been stated by the European Cystic Fibrosis Exercise Working Group . (2) Although maximum ventilation at peak (47.1 L/min) seems to be slightly below values of previous MST studies (ie, 64.0 ± 17.7, 57.7 ± 20.0, 64.0 ± 24.0), as above mentioned, the majority of patients achieved predicted VO 2 peak. (3) External validation should be conducted in future studies, as it requires a different sample.…”
mentioning
confidence: 79%
“…Guidelines recommend exercise testing and prescription from 10 years of age [3], although factors such as physical stature, and cognitive ability to understand the demands of the test, will influence whether a child can, and should, perform CPET [13]. A previous observational study of CPET in clinical practice has shown that young children (7 years) were unable to perform the test due to poor cooperation [4], and therefore testing of children should be considered on a case-by-case basis, as shown by the present review.…”
Section: Discussionmentioning
confidence: 99%
“…Given the importance of identifying and monitoring aerobic fitness, exercise testing is recommended to take place annually [2]. Cardiopulmonary exercise testing (CPET) is acknowledged as the 'gold standard' methodology in CF [3], with this service having been successfully implemented in some CF centres in the United Kingdom (UK) [4].…”
Section: Introductionmentioning
confidence: 99%